Ethan Kleinberg: Theory of History as Hauntology - Ramos, André da Silva (História da Historiografia: International Journal of Theory and History of Historiography, 2018)
Ethan Kleinberg is Professor of History and Letters of Wesleyan University. He is the Director of the Center for Humanities and the Editor-in-Chief of History and Theory. His first book, Generation Existential: Heidegger’s Philosophy in France, 1927-1961, published by Cornell University Press, was awarded the 2006 Morris D. Forkosch prize for the best book in intellectual history, by the Journal of the History of Ideas. Recently, Professor Kleinberg co-edited with Ranjan Ghosh the volume Presence: Philosophy, History and Cultural Theory for the 21st Century, published by Cornell University Press as well. His book, Haunting History: For a Deconstructive Approach to the Past, will appear in the Meridian Series from Stanford University Press in Fall 2017. He is also finishing the book The Myth of Emmanuel Levinas, centered on the Talmudic Lectures that the French-Jewish philosopher presented in Paris between 1960 and 1990. I had the opportunity to conduct an interview with Professor Kleinberg in June 2016, when I was a Visiting Student Researcher in the Center for Humanities at Wesleyan University. We also took the advantage of the Second International Network for Theory of History conference (2nd INTH), that happened in Brazil at Ouro Preto from August 23 to August 26, to expand the interview.